Exploring the Emotional Factors in College English Classroom Teaching Based on Computer-Aided Model - Fen Fu (Advances in Multimedia)
In order to improve the effect of emotional factor analysis in college English classroom teaching, this paper analyzes the emotional factors of college English classroom teaching combined with computer technology and proposes an attribute-level emotional analysis method based on lifelong learning. Moreover, while solving the sparseness of short texts, this paper integrates the three tasks of topic recognition, emotional tendency judgment, and separation of general emotional words and attributes emotional words under the same model framework. In addition, this paper combines lifelong learning to improve the coherence and correctness of topic mining. Finally, this paper improves the teaching process by analyzing students’ emotional intelligence. The data analysis verifies that the computer-aided model based on the emotional factor analysis model of college English classroom teaching has a good effect in the analysis of emotional factors in English classroom teaching and the improvement of classroom teaching effect.